Exchange rate policy in Peru: between pro-export bias and anti-inflationary policy - León Astete, Javier (1989)
In this article, the author states how two types of exchange policies (crawling peg with a parity criterion and a long period-fixed exchange rate), have influenced the evolution of the effective real exchange rate during the last four years. Four doing this, two indicators are used: the induced distortion and the additional variability.